Strategi Pembelajaran Saintifik Dalam Meningkatkan Keterampilan Berfikir Ilmiah Siswa - Lidia; Ahmadin; Muslim (STAI AL-AMIN, 2025)
The background of the problem raised in this study is the importance of developing scientific thinking skills from an early age, which is the basic foundation for mastering science and problemsolving skills, namely developing the ability to observe, experiment, and in-depth analysis so that the learning strategies applied at PAUD Alfasalam can improve children's scientific thinking skills. The research method used is qualitative with a descriptive approach. Data collection techniques were carried out through observation, in-depth interviews, and supporting documents. The data sources in this study were PAUD teachers, students, and relevant documents. Research procedures include direct observation of learning activities that use scientific strategies and interviews with teachers regarding the methods they apply. Data analysis techniques were conducted using a thematic approach, which identified patterns and themes that emerged from observations and interviews. The results showed that the application of scientific learning strategies has effectively improved scientific thinking skills seen in several aspects including student involvement, curiosity, observation ability, analysis ability and scientific thinking skills. The achievement of the application of scientific learning strategies in Alfasalam PAUD cannot be separated from several efforts that have been made by teachers including project-based learning, simple experiments, and utilization of educational game-based media, proven effective in developing children's ability to think critically and analytically.